Interactions between antidepressants, sleep aids and selected breast cancer therapy - Jody Jacobson Wedret; Thanh G. Tu; Doru Paul; Camille Rousseau; Augustin Bonta; Robert G. Bota (Mental Illness, 2019)
Depression and insomnia are very significant pathologies in cancer patients as they contribute to the patient’s overall cure and quality of life. Moreover, untreated depression and ongoing insomnia are associated with decreased immune responses and lower survival rates. With all disease states and especially with cancer, close attention to drug-drug interactions and the potential impact on the efficacy of therapy is paramount. One area of particular interest due to the lack of well-done clinical trials is drug-drug interaction(s) between antidepressants and cancer treatment. Pharmacokinetics of a certain drug allows for prediction of certain drug interactions based on chemical properties of the agents involved. If the agents depend on their metabolites for activity, active drug level will be decreased through this enzyme inhibition. In this paper, we looked at the cytochrome-P450 drug interactions between antidepressants and sleep aids with Selective Estrogen Receptor Modulators (SERM). Newer SERM metabolisms are less influenced by interactions with medications used to treat depression. However, tamoxifen metabolism could be severely altered by several antidepressants. This has direct consequences as patients on tamoxifen and antidepressant can have double the risk of relapse to cancer in two years. We discussed those interactions and made recommendations for clinical use.